2021
DOI: 10.1186/s12963-020-00245-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family planning on maternal mortality in Indonesia: what future contribution can be expected?

Abstract: Background Although efforts to reduce high maternal mortality in countries such as Indonesia tend to focus on addressing health risks among pregnant women, family planning has been shown globally to reduce maternal mortality by reducing both total and higher-risk pregnancies. This article assesses past contributions of family planning to the reduction of maternal mortality in Indonesia and the potential future contribution toward achieving the 2030 SDG maternal mortality goal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 15 publications
1
28
0
6
Order By: Relevance
“…Some of our own specific research questions or specific information that we would like to have couldn't be asked, this means it's not specific to our needs as researchers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…Some of our own specific research questions or specific information that we would like to have couldn't be asked, this means it's not specific to our needs as researchers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…A recent study based on a decomposition analysis showed that the Indonesian family planning program has contributed highly to reducing maternal mortality (Utomo et al, 2021). The analysis showed that the Indonesian family planning program averted 150.5 million births between 1970-2017, a 40.7% reduction in births.…”
Section: Indonesia Evidence Maternal Deaths Decomposition Analysismentioning
confidence: 99%
“…Similarly, increasing the contraceptive prevalence rate means reducing the number of births and, thus, reducing the risk of maternal death per mother. Utomo et al (2021) carried out a simulation to compare declining trends of maternal mortality ratio between 2017-2030 depending on three different situations: (1) continued stabilization of a contraceptive prevalence rate (CPR) of 63% and UNC of 10%;…”
Section: Survival Analysis: Use Of Contraceptive and The Reproductive Aged Women Risk Of Mortalitymentioning
confidence: 99%
“…Indonesia has a success story in family planning program. The contraceptive prevalence rate increased sharply from 8% in the early 1970s to about 60% in 2002 [ 20 ]. In 2017, contraceptive prevalence rate in Indonesia was about 64%.…”
Section: Introductionmentioning
confidence: 99%